Acute exacerbations of chronic obstructive pulmonary disease in a cohort of Chinese never smokers goes along with decreased risks of recurrent acute exacerbation, emphysema and comorbidity of lung cancer as well as decreased levels of circulating eosinophils and basophils - Wang, Guangdong; Ma, Aiping; Zhang, Liang; Guo, Jiaxi; Liu, Qun; Petersen, Frank; Wang, Zhanxiang; Yu, Xinhua (Frontiers in Medicine, 2022)
Acute exacerbations show a significant impact on disease morbidity and mortality in chronic obstructive pulmonary disease (COPD). In contrast to stable COPD, the association of smoking status with clinical and laboratory characteristics in patients with acute exacerbations of COPD (AECOPD) has not been well studied. In this retrospective study, we compared never smokers and ever smokers on their demographic, clinical, and laboratory characteristics in a Chinese clinical cohort of AECOPD. In this cohort comprising 1034 consecutive patients with AECOPD, never smokers were older (75 years vs 70.5 years, padjusted<0.001) and had a higher body mass index than smokers (21.1± 4.0 vs 20.3 ± 3.4, padjusted=0.028). Furthermore, never smokers showed a decreased risk of recurrent acute exacerbation (13.0% vs 21.8%, padjusted=0.029), a lower risk of development of emphysema (77.8% vs 89.1%, padjusted<0.001), a lower prevalence of the co-morbidity of lung cancer (0.5% vs 6.6%, padjusted<0.001), lower levels of circulating eosinophils (0.04x109/L vs 0.10x109/L, padjusted=0.007) and basophils (0.02x109/L vs 0.03x109/L, padjusted=0.019), and a higher plasma levels of D-dimer (0.62 µg/ml vs 0.51 µg/ml, padjusted=0.02).. Furthermore, multivariate logistic regression analysis identified several risk factor for the recurrent acute exacerbation, including smoking (OR=1.84, 95% CI:1.03-3.40, p=0.044), urban residential area (OR=1.43, 95% CI:1.01-2.05, p=0.045) and the presence of emphysema (OR=2.31, 95% CI:1.25-4-69, p=0.012). In conclusion, this study demonstrates that smoking status of patients is associated with the recurrent acute exacerbations, emphysema, lung cancer and levels of circulating eosinophils and basophils in AECOPD. Identification of cigarette smoking as a risk factor for recurrent acute exacerbation supports behavioral intervention of smoking cessation in the management of patients with AECOPD.